Diversity of Santigi (Pemphis acidula J.R.Forst. & G.Forst.), A Mangrove Association in Tomini Bay, Sulawesi, Indonesia - Baderan, Dewi Wahyuni K.; Rahim, Sukirman; Angio, Melisnawati H.; Akbar, Muh. Nur; Jannah, Magfirahtul; Retnowati, Yuliana; Utina, Ramli (Journal of Tropical Biodiversity and Biotechnology, 2024)
Pemphis acidula is a wild plant in rocky or sandy coastal areas and mangrove ecosystems. Different geographic characteristics may affect plant adaptability and have an impact on the emergence of various genotypes. This study was performed to reveal the phenetic relationship and genetic variation of P. acidula in 3 different areas in Tomini Bay, Gorontalo Province, Indonesia. We took 3 samples from each location and analysed them using 14 morphological characters and molecular approaches based on ISSR markers and ITS gene. The results showed that P. acidula on Olele had bigger sizes in some morphological features compared to the plants in other study areas. The phenetic analysis showed that P. acidula at Biluhu and Dulanga were more closely related, although P. acidula at the 3 locations had 100% similarity. Genetic variation analysis showed the highest genetic similarity based on ISSR markers was found in Dulanga and Biluhu samples (76.8%). Phylogenetic based on ITS gene revealed that Olele samples were in the same clade with P. acidula accession from GenBank (genetic distance 0-0.19%), while Biluhu samples were a sister group (genetic distance 24.97-25.03%) even though their percentage identity corresponds to P. acidula (81.34%). Plant adaptation to different habitat conditions may affect the genetic diversity of P. acidula.